Thermoselective phase property of silica tethered with fluorinated chains for controlled 'release' and 'capture' of catalytic fluorous tin species - Jenkins, P; Steele, A; Tsang, S (2003)
The temperature dependent mixing of organic and fluorous phases is one of the key principals of fluorous biphasic systems (FBS). Given the high cost of the perfluorous solvents and their impacts to the environment, it is apparent that elimination of these solvents in bulk quantity in the FBS is advantageous. We report for the first time, the surface coverage of silica with a fluorous solvent like material that traps (at ambient temperatures) and releases (at elevated temperatures) a fluorous tin bromide in organic solvent. Here, we demonstrate the catalytic utilisation of this species for the hydrocyclisation of 6-bromo-1-hexene with NaBH4. © 2002 Elsevier Science B.V. All rights reserved.